2021
DOI: 10.3390/rs13061129
|View full text |Cite
|
Sign up to set email alerts
|

Change of CO Concentration Due to the COVID-19 Lockdown in China Observed by Surface and Satellite Observations

Abstract: The nationwide lockdown due to the COVID-19 pandemic in 2020 reduced industrial and human activities in China. In this study, we investigate atmospheric carbon monoxide (CO) concentration changes during the lockdown from observations at the surface and from two satellites (TROPOspheric Monitoring Instrument (TROPOMI) and Infrared Atmospheric Sounding Interferometer (IASI)). It is found that the average CO surface concentration in 2020 was close to that in 2019 before the lockdown, and became 18.7% lower as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…Zhou et al 25 studied the change in carbon monoxide (CO) concentration in 1375 sites of China during lockdown employing surface-based and satellite-based observations. They found that the average CO surface concentration was reduced by 18.7% with a spatial variation of 8-27%.…”
Section: Carbon Emission/concentration Over the Land Regionmentioning
confidence: 99%
“…Zhou et al 25 studied the change in carbon monoxide (CO) concentration in 1375 sites of China during lockdown employing surface-based and satellite-based observations. They found that the average CO surface concentration was reduced by 18.7% with a spatial variation of 8-27%.…”
Section: Carbon Emission/concentration Over the Land Regionmentioning
confidence: 99%
“…Artificial night time skyglow as a supplement to night time light remote sensing data is affected by air quality [62,63]. Air pollution decreases due to COVID-19 city lockdown [64,65]. However, to our knowledge, the effect of air quality on artificial skyglow has not been quantified.…”
Section: Discussionmentioning
confidence: 99%
“…In another study 23 , they have employed satellite-based data between January and April 2020 and estimated that China's CO2 emissions reduced by 11.5% in comparison to the same period in 2019. The study of Tohjima et al 24 Zhou et al 25 studied the change in carbon monoxide (CO) concentration in 1375 sites of China during lockdown employing surface-based and satellite-based observations. They found that the average CO surface concentration was reduced by 18.7% with a spatial variation of 8-27%.…”
Section: Chinamentioning
confidence: 99%